RP English Vowel and Consonant Changes in the Brummies' English Accent - Mohamed, Hemaidia; Amina, Abdelhadi (Technium Social Sciences Journal, 2021)
This study aims to investigate consonant and vowel changes in the Brummie accent as compared with the ones in the standard variety of English through a comparative descriptive study. The investigation is based on an audio recording conversation and an extract of a TV show film; in addition to a questionnaire administered to 40 second year students of Master degree of linguistics from the English section of Ibn Khaldoun University, after they have been exposed to both the audio recording and the film extract. This is to gather information about their attitudes towards the aforementioned changes’ effects. Thefindings of the current study reveal the existence of great alterations in the articulation of vowel and consonant sounds in Brummie accent, which may differ from the norms that govern the standard variety of English. The outcomes of the audio recording and video extract as well as the gathered data from students’ questionnaire point out negative effects on learners’ clear perception of Brummie accent, which will undoubtedly lead to their fear of confronting serious communication problems when talking with UK citizens.